Utilitas Ragam Media Digital dan Stuktur Persaingan Pasar antar Desa Wisata di Kawasan Perbukitan Menoreh - Antonius Budisusila; Victoria Sundari Handoko (Lasigo Akademia Indonesia, 2023)
The results of previous research on tourism digitization tend to legitimize the success of optimizing tourism digitization. These studies use the